Stepping up to Global Challenges (SGC): Empowering Students across the World - Amante Susana; Antunes Maria José; Dygala Magdalena; Gökçe İlkay (Psychology of Language and Communication, 2021)
Stepping up to Global Challenges (SGC) aimed to provide students with opportunities for language practice through task-based learning activities and the use of digital platforms for interaction. Marketing students at the Polytechnic of Viseu, Portugal, collaborated with peers from Poland and Turkey, choosing an image on entrepreneurship and posting it on the SGC Facebook page to solicit comments from their own and other groups. This was one of the tasks assigned during the 2nd semester of 2019/20, under the constraints of COVID-19. We analyzed the students’ choices, main difficulties, and motivation to persist in learning and improving their skills to share knowledge with (inter)national peers.